2018
DOI: 10.1093/cid/ciy751
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Stability of Resistance to Latent Mycobacterium tuberculosis Infection in Highly Exposed Tuberculosis Household Contacts in Kampala, Uganda

Abstract: Resistance to LTBI, defined by repeatedly negative TST and IGRA, in adults who have had close contact with pulmonary TB patients and live in TB-endemic areas, is a stable outcome of M.tb exposure. Repeated longitudinal measurements with two different immune assays and extended follow-up provide enhanced discriminatory power to identify this resister phenotype and avoid misclassification. Resisters may use immune mechanisms to control aerosolized M.tb that differ from those used by persons who develop "classic"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
113
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(120 citation statements)
references
References 26 publications
2
113
0
5
Order By: Relevance
“…While there were small groups of individuals with conversions and reversions of TST and IGRAs, only HIV negative subjects who remained concordantly negative for all tests (n=82) were defined as “resisters” and used in this analysis (Supplementary Table 1). 11 By extension, HIV negative control subjects with LTBI were defined by consistently positive results at all time points by both IGRA (Extended data Figure 1A) and TST (Extended data Figure 1B and 1C), and no evidence of clinical disease. To balance for confounding factors, a representative subset (Supplementary Table 2) of “resisters” and LTBI controls were matched by age (≥ 15 years), gender and epidemiological risk score (Supplementary Table 1), representing, to our knowledge, the longest followed cohort of “resisters”.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…While there were small groups of individuals with conversions and reversions of TST and IGRAs, only HIV negative subjects who remained concordantly negative for all tests (n=82) were defined as “resisters” and used in this analysis (Supplementary Table 1). 11 By extension, HIV negative control subjects with LTBI were defined by consistently positive results at all time points by both IGRA (Extended data Figure 1A) and TST (Extended data Figure 1B and 1C), and no evidence of clinical disease. To balance for confounding factors, a representative subset (Supplementary Table 2) of “resisters” and LTBI controls were matched by age (≥ 15 years), gender and epidemiological risk score (Supplementary Table 1), representing, to our knowledge, the longest followed cohort of “resisters”.…”
Section: Resultsmentioning
confidence: 92%
“…A subset of healthy, immunocompetent individuals remain TST and IGRA negative despite persistent, high levels of exposure to Mtb 4,5 . Highly Mtb exposed but persistently TST and IGRA negative individuals have been described among health-care workers 6,7 , household contacts of TB cases 811 , and gold miners living and working in close quarters with individuals with active disease 12,13 . These individuals have been dubbed “resisters” related to their persistent ability to remain TST and IGRA negative 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…who do not convert their negative IGRA or TST status, and do not develop TB, despite known high Mtb exposure are generally considered to be also resistant to active TB. These persons have been termed either "resisters" or "early clearers" [2][3][4][5] and several immune and genetic factors have been identified that contribute to this phenotype. [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A subset of healthy, immunocompetent individuals remain TST and IGRA negative despite persistent, high levels of exposure to Mtb 4,5 . Highly Mtb-exposed but persistently TST and IGRA negative individuals have been described among healthcare workers 6,7 , household contacts of patients with TB [8][9][10][11] and gold miners living and working in close quarters with individuals with active disease 12,13 . These individuals have been dubbed 'resisters' related to their persistent ability to remain TST and IGRA negative 4,5 .…”
mentioning
confidence: 99%